A real‐time bus‐subway transfer scheme recommendation systems. (21st May 2018) - Zhang, Jun; Tu, Lai; Zhang, Fan; Huang, Benxiong; Liu, Jin
Summary: Bus and subway service is an important public transportation. Besides the major goal of carrying passengers around, providing accurate and reliable travel information for passengers is also an important business consideration. The route and its traveling time can directly affect the number of people choosing the line. Traditional approaches to obtain route and its traveling time rely on historical experience, which are both non‐scalable and incomplete. The wide adoptions of On Board Units (OBUs) in public transportation provide new opportunities. In this paper, we associate bus GPS data with station locations to derive the traveling time between two stations and make a short forecast. To our best knowledge, this is the first paper that utilizes real‐time bus GPS data and subway arrival station data to design route and give its traveling time for a passenger.